Analysis of the welfare of university students. A case study with psychology students - López-Solís, María; Quizhpi-Criollo, Franco; Tacuri-Reino, René (Maskana, 2021)
From the beginning of the pandemic, the confinement stage has affected various social groups' living conditions, including college students, globally. In many cases, the pandemic has affected their well-being. This research is aimed to analyze university students' well-being during the confinement stage and distinguish its influence from habits, routine, affective relationships, and religious practices. The participants were fifty-two university students from the Faculty of Psychology of the University of Cuenca, who were evaluated through the Ecuadorian Adaptation of the PERMA Profile. The results indicated that the participants presented a good level of well-being with a general mean of 7.95, highlighting the purpose factor. The variables that were significant in relation to the three well-being factors were affective relationships and established routine. In conclusion, the levels of well-being of these university students are good; also, hygiene habits, hobbies, religious practices, exercise practice and eating habits did not prove to be completely influential, however, it turned out that an organized routine and affective relationships favor well-being. These findings suggest expanding new research related to new forms of socialization after the pandemic, further deepening habits, coping strategies and resilience.